2001
DOI: 10.1109/36.957284
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of subpixel hyperspectral targets with continuous and discrete wavelet transforms

Abstract: Abstract-This paper introduces the use of adaptive multichannel discrete wavelet transforms (AMDWTs), allowing for a customized design of optimum mother wavelets, for the detection of a constituent absorption band within a hyperspectral curve. Even when the target's amplitude is only 3% of the background signal's amplitude, the AMDWT approach produces target detection rates of 90%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 22 publications
0
56
0
Order By: Relevance
“…The highest RMSE with q = 10 indicated that the solution closely matching the test dataset might not be the best solution to estimate LAI. We chose the Haar mother wavelet in this study, as it is the simplest of various mother wavelets, and has been found useful for hyperspectral data analysis in previous studies [33,36,39]. Pu and Gong [41] compared different families of wavelets for LAI and crown cover mapping using EO-1 Hyperion data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The highest RMSE with q = 10 indicated that the solution closely matching the test dataset might not be the best solution to estimate LAI. We chose the Haar mother wavelet in this study, as it is the simplest of various mother wavelets, and has been found useful for hyperspectral data analysis in previous studies [33,36,39]. Pu and Gong [41] compared different families of wavelets for LAI and crown cover mapping using EO-1 Hyperion data.…”
Section: Discussionmentioning
confidence: 99%
“…We chose the Haar mother wavelet as it is the simplest of all available mother wavelets, and recent investigations have illustrated its effectiveness in hyperspectral data analysis [33,36,39]. The decomposition level is determined by the type of wavelet and the original signal length.…”
Section: Calculation Of Discrete Wavelet Coefficientsmentioning
confidence: 99%
See 2 more Smart Citations
“…From previous research in wavelet analysis of hyperspectral signatures, we know that large scale, or global features, can be pertinent to particular target recognition problems. For example, the discrete wavelet transform (DWT) has been successfully used for extracting both local and global spectral features in several hyperspectral target recognition systems [3][4][5][6][7][8]. Bruce et al used the DWT to successfully extract features from hyperspectral signatures [3][4], and interestingly, they found that oftentimes a combination of both small scale and large scale features were optimum.…”
Section: Introductionmentioning
confidence: 99%